Color Selection and Reproduction in Dentistry Part 2: Light Dynamics in Natural Teeth - Schmeling DDS, MS, PhD, Max (2016)
In the first article of this trilogy, it was demonstrated the great importance of the light source in the chromatic procedures and also the chromatic characteristics of color communication proposed by Munsell.  In this second article, the focus is in Geometric Attributes and Optical Properties of natural teeth. The main features of translucency, opalescence and fluorescence will be described. According to the interaction of light with natural dental tissues, the desired optical qualities of the esthetic restorative materials will be associated.